Identification and characterization of gonadotropin-releasing hormone (GnRH) in Zhikong scallop Chlamys farreri during gonadal development - Tang, Juyan; Yuan, Mengqiang; Wang, Jia; Li, Qianqian; Huang, Baoyu; Wei, Lei; Liu, Yaqiong; Han, Yijing; Zhang, Xuekai; Wang, Xiaona; Zhang, Meiwei; Wang, Xiaotong (Frontiers in Physiology, 2023)
Gonadotropin-releasing hormone (GnRH) controls synthesis of sex steroid hormones through hypothalamic-pituitary-gonadal (HPG) axis in vertebrates. But in mollusks, research on neuroendocrine control of gonadal function, such as the function of GnRH during gonadal development is limited. In this study, we investigated the morphology and structure of the nerve ganglia of Zhikong scallop Chlamys farreri by physiological and histological observations. We also cloned the ORF and studied the expression patterns of GnRH in the scallop. Tissue expression analysis showed that GnRH was highly expressed in parietovisceral ganglion (PVG). The in situ hybridization result further confirmed that GnRH mRNA only distributed in some good-sized neurons in the posterior lobe (PL) and some pint-sized neurons in the lateral lobe (LL). In addition, by examining the expression of GnRH during gonadal development in ganglia, we found GnRH displayed higher expression in the female scallops and showed significant high expression at the growing stage of female scallops in PVG. This study would contribute to gaining insight into the mechanism underlying reproduction regulation by GnRH in the scallop and help to provide a better understanding of reproductive neuroendocrine in mollusks.